(untitled) (Medical Forum Monthly, 2023)
Objective: The objective of this study to evaluate pregnancy rate in polycystic ovary syndrome patient with effect of letrozole versus clomiphene citrate, Mirpur AJK Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Department of Obstetrics and Gynecology MBBS Medical College Mirpur AJK and Mohi-Ud-Din Islamic Medical College, Mirpur AJ&K from May 2022 to January 2023. Materials and Methods: This study is a retrospective comparative analysis involving 400 infertile patients. The standard protocols for Ovulation Induction (OI) in infertile patients with PCOS were Clomiphene Citrate (CC) or Letrozole (LTZ). The patients were thoroughly briefed about the mechanisms and experiential effects of LTZ, including its off-label application. The use of LTZ was based on the couples' preference. The patients were categorized into two groups: the CC group (n=200) and the LTZ group (n=200). In the CC group, patients were administered 50 mg of CC twice daily, while in the LTZ group, patients were given 2.5 mg of LTZ twice daily Results: When evaluating the ovulation rate per menstrual cycle, the LTZ group (94.1%) outperformed the CC group (84.8%), demonstrating statistical significance (p=0.013). In terms of clinical pregnancy rates, the LTZ group exhibited a rate of 53%, while the CC group displayed a rate of 43.2%, with the former exhibiting a statistically superior outcome (p=0.047). Conclusion: In conclusion, the utilization of LTZ as an ovarian induction agent proves to be efficacious among individuals diagnosed with Polycystic Ovary Syndrome (PCOS). Notably, LTZ exhibits a notable advantage over CC, particularly concerning both pregnancy rates and the rates of successful live births. Given these findings, we propose that LTZ be prioritized as the primary therapeutic choice for treating PCOS patients.